Anchoring clamping device suitable for torsion test of composite rod system component and using method of anchoring clamping device

The anchoring and clamping device, consisting of an end plate, a limiting sleeve, and a pin, solves the problem of the applicability of traditional torsion testing devices to non-metallic materials, realizes the stable fixation and torque transmission of composite material rod components, and ensures the accuracy and reliability of test results.

CN120800983APending Publication Date: 2025-10-17WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510985108.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing torsion testing devices are mainly designed for traditional metallic materials, making it difficult to effectively fix and transmit torque to new non-metallic materials such as FRP and ECC. This results in inaccurate and unreliable test results, and traditional anchoring methods are prone to slippage or local crushing.

Method used

An anchoring and clamping device consisting of an end plate, a limiting sleeve, and a pin is used to achieve stable fixation and torque transmission of composite material rod components by using a rubber gasket in the fit between the limiting sleeve and the pin hole, thus avoiding stress concentration.

Benefits of technology

It enables accurate torsional performance testing of composite material rod systems, avoiding the slippage and crushing problems of traditional anchoring methods. It has a wide range of applications, is easy to operate, and provides highly reliable data.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120800983A_ABST
    Figure CN120800983A_ABST
Patent Text Reader

Abstract

The invention provides an anchoring and clamping device suitable for a torsion test of a composite rod system component and a using method of the anchoring and clamping device, and belongs to the technical field of new material tests of building structures. The device comprises a pair of end plates, a pair of limiting sleeves and a bolt pin. During use, the first bolt pin hole channel is formed in the end of the rod system component, and after the first bolt pin hole channel is aligned with the second bolt pin hole channel in the limiting sleeve, a bolt pin sleeved with a rubber pad sleeve is inserted to achieve fixation. The device solves the problem that a traditional metal material torsion test device cannot be matched with non-metal materials such as FRP and ECC, and through reinforcement of the limiting sleeve, stress dispersion of the bolt pin and buffering of the rubber cushion cover, torque can be stably transmitted, and slippage, crushing and interface bonding damage can be avoided. The device is simple in structure, wide in application range and convenient to operate, the torsion performance of the composite rod system component can be accurately tested, it is guaranteed that bonding of all material interfaces of an anchoring clamping part is not damaged, and reliable test data support is provided for engineering application of novel building materials.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of new material testing of building structures, and particularly relates to an anchoring and clamping device suitable for torsional testing of composite material rod system components and a use method thereof. BACKGROUND

[0002] In building structure design and safety evaluation, torsional performance is one of the important indicators for measuring the mechanical behavior of beams, columns and other components. Structural components may be subjected to complex torque in actual use, such as earthquakes, wind loads or asymmetric loads, etc. If the torsional bearing capacity is insufficient, it may lead to component failure and affect the safety of the overall structure. Therefore, accurately determining the torsional stiffness, ultimate torque and failure mode of the component through torsional testing is of great significance to structural design and optimization, theoretical model verification, etc. At present, relevant specifications at home and abroad also clearly require the torsional testing method of structural components.

[0003] In recent years, with the rapid development of material science, high-performance non-metallic materials such as fiber-reinforced composites (FRP) and fiber cement-based materials (ECC) are increasingly widely used in building structures. Such materials have the advantages of lightweight, high strength, corrosion resistance, and strong designability, and are suitable for fields such as bridge reinforcement, marine engineering and prefabricated buildings. For example, FRP bars can replace steel bars to solve the problem of corrosion, and fiber cement-based materials can significantly improve the crack resistance and toughness of components. However, the existing torsional testing devices are mainly designed for traditional metallic materials (such as steel, aluminum, etc.), and the anchoring method of the component ends during the test usually relies on welding or bolt connection, which is difficult to adapt to the testing needs of new non-metallic materials. At the same time, the mechanical properties of these new non-metallic materials are significantly different from traditional metallic materials, especially in terms of anisotropy and brittle failure in torsional behavior. Therefore, there is a growing demand for torsional testing of such new building materials, but due to the limitations of the anchoring method, the existing testing devices are difficult to achieve effective fixation and torque transmission of the test specimen, which restricts the in-depth study of the mechanical properties and the promotion of engineering applications.

[0004] At present, the anchoring and clamping devices commonly used in building structure torsional testing are mostly designed based on metallic test specimens, and the typical method is to fix the two ends of the test specimen on the torsional testing machine through welding or high-strength bolts. For example, steel beams can be directly welded to the fixture, and concrete test specimens need to be pre-buried with steel sleeves or bolt holes. However, for non-metallic materials such as FRP and ECC, welding is not feasible, and pre-buried metal parts will change the local stress distribution of the test specimen, affecting the authenticity of the test. In addition, such new building materials often have smooth surfaces or hard and brittle textures, and traditional mechanical clamping may cause slippage or local crushing, making it difficult to achieve uniform torque transmission. Although a few studies have attempted to use adhesive or wrapping anchoring, there are problems such as bonding failure and complex operation.

[0005] Therefore, it is urgent to develop a torsion test model anchoring and clamping device which can meet the torsion test requirements of new non-metallic material components, has simple technical operation, and can ensure that the bonding of the material interfaces at the anchoring and clamping parts is not damaged, so as to ensure the accuracy and repeatability of test data. SUMMARY

[0006] One of the purposes of the present application is to provide an anchoring and clamping device which is simple in structure, widely applicable, simple in technical operation, can ensure that the bonding of the material interfaces at the anchoring and clamping parts is not damaged, and is widely applicable to torsion tests of various composite material rod system components.

[0007] The second purpose of the present application is to provide a use method of an anchoring and clamping device which is simple in structure, widely applicable, simple in technical operation, can ensure that the bonding of the material interfaces at the anchoring and clamping parts is not damaged, and is widely applicable to torsion tests of various composite material rod system components.

[0008] The technical solution adopted by one of the purposes of the present application is to provide an anchoring and clamping device applicable to torsion tests of composite material rod system components, comprising: a pair of end plates for transmitting torque to the rod system component; a pair of first pin bolt holes are symmetrically arranged on the side walls near the two ends of the rod system component; a pair of limiting sleeves fixedly connected with the two end plates and sleeved on the end portions of the rod system component; a second pin bolt hole is arranged on the side wall of the limiting sleeve corresponding to the first pin bolt hole; a pin bolt which passes through the second pin bolt hole and enters the first pin bolt hole, and is used for fixing the limiting sleeve and the end portion of the rod system component; a rubber pad sleeve is sleeved on the part of the pin bolt in contact with the inner wall of the first pin bolt hole.

[0009] The present application provides a new anchoring and clamping device for torsion tests, which places the rod system component with the first pin bolt hole arranged on the end portion between the clamping device composed of the end plate and the limiting sleeve, and arranges the second pin bolt hole on the limiting sleeve corresponding to the first pin bolt hole, and fixes the two by the pin bolt passing through the first pin bolt hole and the second pin bolt hole, so as to transmit the torque to the rod system component through the end plate, and realize the torsion performance test of the composite material rod system component.

[0010] Further, in order to ensure that the bonding of the interfaces of the composite material is not damaged, the present application provides a rubber pad sleeve at the position where the pin bolt contacts the inner wall of the first pin bolt hole, and the pin bolt fills the first pin bolt hole with interference fit. On the one hand, it can ensure that the surface of the pin bolt closely contacts the inner wall of the hole, and the load transmission is as uniform as possible in the radial length of the pin bolt, so that the stress of each layer of material in the depth direction of the hole is uniform. On the other hand, the pin bolt closely contacts the inner diameter of the hole under the cooperation of the rubber pad sleeve, and the hole has a larger contact area with the pin bolt in the hoop direction, so that stress concentration is avoided and the hole is not crushed during loading to cause material delamination.

[0011] Further, the rod system component of the present application is a test piece made of composite material that cannot be connected to the end plate by welding. It includes a composite rod system component with interlayer interface bonding in the radial direction of the cross section, and a composite rod system component that cannot be connected to the end plate of the anchoring and clamping device by welding. Specifically, the material of the rod system component includes one or a combination of ordinary concrete, fiber concrete, fiber cement-based material, and fiber reinforced composite material. The fibers include non-metallic fiber materials such as glass fiber, basalt fiber, polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber, etc., and various steel fibers.

[0012] Further, in order to prevent end effect, the length of the rod system component is greater than twice its diameter. The diameter of the first pin bolt hole should not be too small to avoid stress concentration, and preferably the diameter of the first pin bolt hole is 0.3-0.6 times the diameter of the rod system component. The first pin bolt hole should not be too deep to avoid excessive weakening of the cross section, and preferably the depth of the first pin bolt hole is 0.2-0.3 times the diameter of the rod system component. In addition, in order to prevent damage to the hole wall during torsion testing, the distance between the center of the first pin bolt hole and the adjacent end of the rod system component is preferably 1-1.5 times the diameter of the first pin bolt hole.

[0013] Further, the end plate is made of steel material and needs to have sufficient thickness to meet the requirement of torsional stiffness, and preferably the thickness of the end plate is ≥10mm. Preferably, the end plate is quadrangular, and four corners of the end plate are provided with an anchor hole group for connecting with the torsion test equipment. The anchor hole group is used to connect the end plate of the anchoring and clamping device with the torsion test equipment through a bolt group, to ensure stable transmission of the loading moment to the torsion test model of the rod system component.

[0014] Further, the limiting sleeve is made of steel material, and is connected with the end plate in a welded manner to form an integrated structure, and the material of the end plate and the limiting sleeve is steel material, so as to be unified with the material of other test loading equipment. In order to prevent the limiting sleeve from being deformed in the torsion test and affecting the test results, preferably, the ratio of the diameter of the limiting sleeve to the wall thickness thereof is ≤15. In order to satisfy the strengthening effect on the end part of the hole weakening test piece, preferably, the height of the limiting sleeve is 2-3 times of the diameter of the first pin hole.

[0015] Further, the diameter of the second pin hole is the same as that of the first pin hole, and the distance between the lower edge of the second pin hole and the edge of the limiting sleeve is not less than 0.5 times of the diameter of the second pin hole, so as to prevent the pin from forming a lever to cause stress concentration.

[0016] Further, the pin is made of steel material, and the pin has a circular cross section, so that the stress distribution is more uniform and the change is more moderate, and the stress concentration is reduced. The ratio of the diameter of the pin to the diameter of the first pin hole is 0.9-0.95; the pin is filled in the first pin hole in an interference fit under the cooperation of the rubber pad sleeve, so as to ensure that various materials of the pin and the inner wall of the first pin hole of the bar member are uniformly contacted, and the interface bonding of various materials in the test is reliable and cooperates. Preferably, the difference between the diameter of the pin with the rubber pad sleeve and the diameter of the first pin hole is controlled to be within 5 mm, so as to avoid that the pad sleeve is deformed too much to cause the pin to form a lever to cause stress concentration.

[0017] Further, the end part of the pin abuts against the deepest part of the first pin hole in use, and the length of the pin is not less than the distance from the deepest part of the first pin hole to the outer wall of the limiting sleeve.

[0018] Further, through the test, the pad sleeve on the pin should use relatively hard rubber with certain buffering performance and excellent elasticity, and cannot use soft silica gel which is easy to be deformed. Otherwise, the pad sleeve is deformed too much in the test, loses the dispersion effect of the load transmitted to the pin from the hole, and still causes the material at the hole to be crushed due to stress concentration. Preferably, the rubber pad sleeve is made of rubber with Shore A hardness of 60-80, tensile strength ≥15 MPa, and compression permanent deformation rate ≤20%, and the thickness thereof is 1-5 mm.

[0019] In the present application, based on the calculation method of the interlaminar bonding strength characteristics and the shear bearing capacity of the composite material, the structural size of the anchoring and clamping device is optimized and designed, so as to better satisfy the test requirements of the torsion test of the composite material bar member. Further, before actual use, the bearing capacity calculation formula should be used for checking, and the specific size parameters should be checked.

[0020] The technical scheme adopted by the second object of the present application is to provide a use method of the anchoring and clamping device for the torsion test of the composite material rod system component according to the first object of the present application, comprising the following steps: S1, a first pin hole is formed in the side wall near the two ends of the rod system component to be tested; S2, end plates with limiting sleeves are respectively sleeved on the two ends of the rod system component, and the second pin hole of the limiting sleeve is aligned with the first pin hole; S3, four pins sleeved with rubber pad sleeves are respectively inserted into the first pin hole through the second pin hole, and reach the end of the first pin hole; S4, the torsion test model composed of the anchoring and clamping device and the rod system component is connected with the compression-torsion test equipment through the end plate, and then the test loading is performed.

[0021] Compared with the prior art, the present application has the following advantages: (1) The anchoring and clamping device for the torsion test of the composite material rod system component comprises an end plate, a limiting sleeve and a pin. The end plate is used to connect with the torsion test equipment and transmit torque to the rod system component. The internal space shape of the limiting sleeve is consistent with the cross section of the test piece. The pin is designed in a circular cross section and is provided with a rubber pad sleeve to optimize the contact stress distribution. In use, first, the first pin hole group with an inner diameter matching the outer diameter of the pin is machined on the two ends of the rod system test piece, then the end plate and the limiting sleeve are sleeved on the two ends of the test piece, the second pin hole group of the limiting sleeve is aligned with the first pin hole group and the pin is inserted, and finally the above-mentioned combination is connected with the test equipment through the anchor hole group of the end plate to load the test. The anchoring and clamping device can stably transmit torque and avoid the problems of slippage, crushing and interface bonding damage caused by traditional welding or bolt anchoring, thereby ensuring the accuracy of the test results, through the reinforcing effect of the limiting sleeve on the end of the test piece, the stress dispersion characteristics of the circular cross section of the pin and the elastic buffering of the rubber pad sleeve.

[0022] (2) The anchoring and clamping device for the torsion test of the composite material rod system component solves the problem that the traditional torsion test device is mainly designed for metal materials and relies on welding or pre-buried metal parts for anchoring, which is difficult to adapt to the smooth or brittle hard surface of non-metallic materials such as FRP and ECC, and is prone to change the test piece failure mode due to stress concentration. The present application has the advantages of simple structure, no need for complex welding or pre-buried process, wide application range, compatibility with metal, concrete, FRP, ECC and other materials, convenient operation, high installation efficiency and reusability, strong data reliability, and true reflection of the torsion performance of the middle part of the test piece while avoiding the interference of the stress concentration at the end. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1The overall structural schematic diagram of the anchoring and clamping device suitable for the torsion test of the composite material rod system component is provided for the embodiment of the present application. Figure 2 The structural schematic diagram of the rod system component in the anchoring and clamping device is provided for the embodiment of the present application. Figure 3 The structural schematic diagram of the end plate in the anchoring and clamping device is provided for the embodiment of the present application. Figure 4 The structural schematic diagram of the limiting sleeve in the anchoring and clamping device is provided for the embodiment of the present application. Figure 5 The structural schematic diagram of the pin bolt in the anchoring and clamping device is provided for the embodiment of the present application. Figure 6 The physical diagram of the rod system component after the torsion test in the embodiment 1 of the present application; wherein (a) is that the typical spiral white streaks appear in the middle of the GFRP sleeve of the GFRP pipe steel fiber recycled concrete column after the torsion test; (b) and (c) are that the typical oblique 45° cracks develop in the middle section of the internal steel fiber recycled concrete part of the GFRP pipe steel fiber recycled concrete column after the torsion test. The physical diagram of the rod system component after the torsion test in the embodiment 1 of the present application; wherein (a) is that the typical spiral white streaks appear in the middle of the GFRP sleeve of the GFRP pipe steel fiber recycled concrete column after the torsion test; (b) and (c) are that the typical oblique 45° cracks develop in the middle section of the internal steel fiber recycled concrete part of the GFRP pipe steel fiber recycled concrete column after the torsion test. DETAILED DESCRIPTION

[0024] The technical solutions of the present application will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present application.

[0025] It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0026] Please refer to Figure 1 The anchoring and clamping device suitable for the torsion test of the composite material rod system component is provided by the embodiment of the present application, which comprises: a pair of end plates 2 for transmitting the torque to the rod system component 1; a pair of first pin bolt holes 11 are symmetrically opened on the side walls of the rod system component 1 close to the two ends; a pair of limiting sleeves 3 are respectively fixedly connected with the two end plates 2 through welding and are sleeved on the end portions of the rod system component 1; the second pin bolt holes 31 are opened on the side walls of the limiting sleeves 3 at the positions corresponding to the first pin bolt holes 11; the pin bolts 4 pass through the second pin bolt holes 31 and enter the first pin bolt holes 11, which are used for fixing the limiting sleeves 3 and the end portions of the rod system component 1; the part of the pin bolts 4 in contact with the inner walls of the first pin bolt holes 11 is sleeved with the rubber pad sleeves 41.

[0027] As Figure 2 shown, the rod system component 1 includes a composite rod system component with interlayer interface bonding in the radial direction of the cross section, and a composite rod system component that cannot be connected to the end plate of the anchoring clamping device through welding due to the non-radial layering of the cross section. The length of the rod system component 1 is greater than twice its diameter; the axis of the first pin hole 11 is perpendicular to the longitudinal axis of the rod system component, and the distance from the center of the two first pin holes 11 to the end face is equal; the diameter of the first pin hole 11 is 0.3-0.6 times the diameter of the rod system component 1, and the depth of the first pin hole 11 is 0.2-0.3 times the diameter of the rod system component 1; the distance between the center of the first pin hole 11 and the adjacent end of the rod system component 1 is 1-1.5 times the diameter of the first pin hole 11.

[0028] As Figure 3 shown, the end plate 2 is made of steel material, and the thickness is ≥10mm; the end plate 2 is quadrilateral, and the four corners are provided with anchor hole groups 21 for connecting with the torsion test equipment.

[0029] As Figure 4 shown, the limiting sleeve 3 is made of steel material; the ratio of the diameter of the limiting sleeve 3 to the wall thickness is ≤15; the height of the limiting sleeve 3 is 2-3 times the diameter of the first pin hole 11. The diameter of the second pin hole 31 is the same as that of the first pin hole 11, and the distance between the edge of the second pin hole 31 and the edge of the limiting sleeve 3 is not less than 0.5 times the diameter of the second pin hole 31.

[0030] As Figure 5 shown, the pin 4 is made of steel material, and the ratio of the diameter of the pin 4 to the diameter of the first pin hole 11 is 0.9-0.95; the pin 4 is filled in the first pin hole 11 with interference under the cooperation of the rubber pad sleeve 41. The end of the pin 4 abuts against the deepest part of the first pin hole 11 during use, and the length of the pin 4 is not less than the distance from the deepest part of the first pin hole 11 to the outer wall of the limiting sleeve 3. The rubber pad sleeve 41 is made of rubber with a Shore A hardness of 60-80, a tensile strength ≥15MPa, and a compression permanent deformation rate ≤20%, and the thickness is 1-5mm.

[0031] The use method of the anchoring clamping device suitable for the torsion test of the composite rod system component provided by the embodiment of the present application comprises the following steps: Step 1: First pin holes 11 are opened in the side walls of the rod system component 1 at both ends, and are checked and cleaned to ensure that the inner surface of the first pin hole 11 is smooth; Step 2: The end plate 2 with the limiting sleeve 3 is sleeved on the two ends of the rod system component 1 respectively, and the second pin hole 31 of the limiting sleeve 3 is aligned with the first pin hole 11. Step 3: Insert four dowels 4 through the second dowel hole group 31 into the first dowel hole group 11 to the end of the first dowel hole group 11. Step 4: Connect the torsion test model composed of the anchoring clamping device and the truss member 1 to the compression-torsion test equipment through the anchor hole group 21 of the end plate 2, and then perform test loading.

[0032] The application will be further described in conjunction with specific examples, but not as a limitation of the application.

[0033] Example 1 The truss member torsion test model 1 is a circular cross-section GFRP (glass fiber reinforced composite material) steel fiber recycled concrete column torsion test piece, with a length of 450 mm, an internal steel fiber recycled concrete part with a diameter of 125 mm, and a GFRP sleeve thickness of 3 mm, 4 mm and 5 mm respectively; the steel fiber recycled concrete strength grade is C50, and the GFRP material yield strength is 400 MPa; the hole center distance of the dowel hole group 11 is 50 mm from the end, the diameter is 50 mm, and the depth is 30 mm. The end plate 2 of the anchoring clamping device has a side length of 290 mm and a thickness of 10 mm, and the anchor hole diameter of the anchor hole group 21 at the four corners is 32 mm; the inner diameter of the limiting sleeve 3 is 139 mm, the thickness is 10 mm, the height is 100 mm, and the hole center of the sleeve dowel hole group 31 is located at half the height of the limiting sleeve 3, with a diameter of 50 mm; the dowel 4 is one pair, with a diameter of 45 mm, a length of 50 mm, a rubber pad sleeve 41 thickness of 1 mm, and a length of 30 mm.

[0034] Through the test, the truss member torsion test model 1 did not have end damage, the dowel hole group 11 did not have damage, and the sleeve dowel hole group 31 had no visible deformation. As shown in Figure 6 (a), typical spiral white streaks appeared in the middle of the GFRP sleeve; as shown in Figure 6 (b) and Figure 6 (c), typical 45° diagonal cracks developed in the middle section of the internal steel fiber recycled concrete part, and the damage patterns of the inner and outer layers of the material corresponded to each other, and the performance of the joint work was good.

[0035] In Example 1, the torsion performance test results of the truss member torsion test model 1 with different thicknesses of the outer GFRP are shown in Table 1 as follows: Table 1

[0036] Example 2 The torsion test model 1 of the truss member is a circular-section GFRP (glass fiber reinforced composite material) ordinary concrete column torsion test piece, 450 mm long, 125 mm in diameter of the internal ordinary concrete part, and 4 mm thick of the outer GFRP tube; the ordinary concrete strength grade is C50, and the GFRP material yield strength is 400 MPa; the hole center of the pin bolt hole group 11 is 50 mm away from the end, 50 mm in diameter, and 30 mm in depth. The end plate 2 of the anchoring clamping device is 290 mm in side length and 10 mm in thickness, the anchor hole diameter of the anchor hole group 21 at four corners is 32 mm; the inner diameter of the limiting sleeve 3 is 139 mm, the thickness is 10 mm, the height is 100 mm, and the hole center of the sleeve pin bolt hole group 31 is located at half of the height of the limiting sleeve 3, and the diameter is 50 mm; the pin bolt 4 is a pair, 45 mm in diameter, 50 mm in length, 1 mm in thickness of the rubber pad sleeve 41, and 30 mm in length.

[0037] Through the test, the torsion test model 1 of the truss member does not have end damage, the pin bolt hole group 11 does not have damage, and the sleeve pin bolt hole group 31 has no visible deformation; the typical spiral white streaks appear in the middle of the GFRP sleeve, the GFRP sleeve is cut open, the spiral cracks develop in the corresponding position in the middle of the internal ordinary concrete part, the damage forms of the inner and outer layers of materials are relatively corresponding, and the common working performance is good; the torsion bearing capacity of the torsion test model 1 of the truss member is 15.6 kN·m, and the corresponding surface linear displacement is 15.7 mm.

[0038] Example 3 The torsion test model 1 of the truss member is a circular-section GFRP (glass fiber reinforced composite material) recycled concrete column torsion test piece, 450 mm long, 125 mm in diameter of the internal recycled concrete part, and 4 mm thick of the outer GFRP tube; the recycled concrete strength grade is C50, and the GFRP material yield strength is 400 MPa; the hole center of the pin bolt hole group 11 is 50 mm away from the end, 50 mm in diameter, and 30 mm in depth. The end plate 2 of the anchoring clamping device is 290 mm in side length and 10 mm in thickness, the anchor hole diameter of the anchor hole group 21 at four corners is 32 mm; the inner diameter of the limiting sleeve 3 is 139 mm, the thickness is 10 mm, the height is 100 mm, and the hole center of the sleeve pin bolt hole group 31 is located at half of the height of the limiting sleeve 3, and the diameter is 50 mm; the pin bolt 4 is a pair, 45 mm in diameter, 50 mm in length, 1 mm in thickness of the rubber pad sleeve 41, and 30 mm in length.

[0039] The end part of the torsion test model 1 of the rod system component does not break, the pin hole group 11 does not break, and the sleeve pin hole group 31 does not have visible deformation; the GFRP sleeve has typical spiral white marks in the middle part, the GFRP sleeve is cut open, spiral cracks develop in the corresponding position in the middle part of the internal basalt fiber recycled concrete part, the damage forms of the inner and outer layers of materials correspond to each other, and the performance of the components is good; the torsion bearing capacity of the torsion test model 1 of the rod system component is 14.4 kN·m, and the corresponding surface linear displacement is 16.7 mm.

[0040] Example 4 The torsion test model 1 of the rod system component is a circular section GFRP (glass fiber reinforced composite material) basalt fiber recycled concrete column torsion test piece, with a length of 450 mm, an internal basalt fiber recycled concrete part with a diameter of 125 mm, and a GFRP pipe with a thickness of 4 mm; the basalt fiber recycled concrete has a strength grade of C50, and the GFRP material has a yield strength of 400 MPa; the hole center distance of the pin hole group 11 from the end part is 50 mm, the diameter is 50 mm, and the depth is 30 mm. The end plate 2 of the anchoring and clamping device has a side length of 290 mm and a thickness of 10 mm, and the anchor hole group 21 of the four corners has an anchor hole diameter of 32 mm; the limiting sleeve 3 has an inner diameter of 139 mm, a thickness of 10 mm, and a height of 100 mm, and the hole center of the sleeve pin hole group 31 is located at half the height of the limiting sleeve 3, with a diameter of 50 mm; the pin 4 is a pair of pins with a diameter of 45 mm and a length of 50 mm, and the rubber pad sleeve 41 has a thickness of 1 mm and a length of 30 mm.

[0041] The end part of the torsion test model 1 of the rod system component does not break, the pin hole group 11 does not break, and the sleeve pin hole group 31 does not have visible deformation; the GFRP sleeve has typical spiral white marks in the middle part, the GFRP sleeve is cut open, spiral cracks develop in the corresponding position in the middle part of the internal basalt fiber recycled concrete part, the damage forms of the inner and outer layers of materials correspond to each other, and the performance of the components is good; the torsion bearing capacity of the torsion test model 1 of the rod system component is 14.4 kN·m, and the corresponding surface linear displacement is 16.7 mm.

[0042] From the above embodiments, the anchoring and clamping device provided by the present application solves the problem of the limitations of traditional torsion test devices in composite material testing through the cooperative design of the end plate, the limiting sleeve and the pin bolt. The device also has the following advantages: (1) wide applicability: it can be adapted to non-metallic new material components represented by FRP-concrete composite columns (ordinary concrete, recycled concrete, steel fiber / basalt fiber reinforced concrete and other different core materials), and can stably transmit torque, avoiding end slip or crushing; (2) accurate test performance: the failure of all test pieces in embodiments 1-4 occurs in the middle (spiral cracks), without abnormal failure at the end or anchoring area, proving that the device can truly reflect the torsional performance of the test piece and avoid test errors; (3) high efficiency and repeatability: the device is modularized and assembled without welding or pre-buried, and is easy to install, suitable for batch testing; the limiting sleeve, end plate and pin bolt can be reused, reducing test cost.

[0043] In summary, the anchoring and clamping device provided by the present application provides a standardized test scheme for the torsional performance research of composite material rod system components (such as FRP-concrete components, fiber reinforced composite material components, etc.), and is especially suitable for the optimization design of non-metallic components with layered cross-sections composed of FRP sleeves and new materials such as recycled concrete and fiber modified concrete. With the anchoring and clamping device provided by the present application, by comparing the test data of test pieces with different parameters (such as FRP pipe wall thickness, fiber type), the material selection and structural design in actual engineering can be accurately guided, and the application of composite materials in seismic and torsional scenarios can be promoted. The present application has both theoretical rigor and engineering practicality, and provides a reliable and efficient solution for composite material torsion tests.

[0044] The above is only the preferred embodiment of the present application, and does not limit the implementation and protection scope of the present application. For those skilled in the art, it should be realized that any equivalent replacement and obvious change made by applying the content of the present application should be included in the protection scope of the present application.

Claims

1. An anchor clamping device suitable for torsion testing of composite rod components, characterized in that: include: A pair of end plates (2) are used to transmit torque to the rod-type component (1); a pair of first pin holes (11) are symmetrically provided on the side walls of the rod-type component (1) near both ends; A pair of limiting sleeves (3) are respectively fixedly connected to the end plates (2) on both sides and sleeved on the end of the rod system component (1); a second pin hole (31) is provided at a position on the side wall of the limiting sleeve (3) corresponding to the first pin hole (11); A pin (4) passes through the second pin hole (31) and enters the first pin hole (11), and is used to fix the limiting sleeve (3) and the end of the rod component (1); the portion of the pin (4) that contacts the inner wall of the first pin hole (11) is provided with a rubber bushing (41).

2. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 1, characterized in that: The rod system components (1) include composite rod system components with interlayer interface bonding in the radial direction of the cross section, and composite rod system components with radial stratification in the non-extended cross section that cannot be connected to the end plate of the anchoring clamping device by welding.

3. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 1, characterized in that: The length of the rod component (1) is greater than twice its diameter; the diameter of the first pin hole (11) is 0.3-0.6 times the diameter of the rod component (1); the depth of the first pin hole (11) is 0.2-0.3 times the diameter of the rod component (1); and the distance between the center of the first pin hole (11) and the end of the adjacent rod component (1) is 1-1.5 times the diameter of the first pin hole (11).

4. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 1, characterized in that: The end plate (2) is made of steel and has a thickness of ≥10 mm. The end plate (2) is quadrilateral, and anchor hole groups (21) for connecting to a torsion test device are provided at its four corners.

5. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 1, characterized in that: The limiting sleeve (3) is made of steel; the ratio of the diameter of the limiting sleeve (3) to its wall thickness is ≤15; and the height of the limiting sleeve (3) is 2-3 times the diameter of the first pin hole (11).

6. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 5, characterized in that: The diameter of the second pin hole (31) is the same as the diameter of the first pin hole (11), and the distance between the lower edge of the second pin hole (31) and the edge of the limiting sleeve (3) is not less than 0.5 times the diameter of the second pin hole (31).

7. The anchoring and clamping device suitable for torsion testing of composite material bar components according to claim 1, characterized in that: The pin (4) is made of steel, and the ratio of the diameter of the pin (4) to the diameter of the first pin hole (11) is 0.9-0.95; the pin (4) performs interference filling of the first pin hole (11) in cooperation with the rubber bushing (41).

8. The anchoring and clamping device suitable for torsion testing of composite bar components according to claim 7, characterized in that: When in use, the end of the pin (4) abuts against the deepest part of the first pin hole (11), and the length of the pin (4) is not less than the distance from the deepest part of the first pin hole (11) to the outer wall of the limiting sleeve (3).

9. The anchoring and clamping device suitable for torsion testing of composite bar components according to claim 7, characterized in that: The rubber gasket (41) is made of rubber with a Shore A hardness of 60-80, a tensile strength of ≥15 MPa, and a compression permanent deformation rate of ≤20%, and has a thickness of 1-5 mm.

10. A method for using the anchor clamping device according to any one of claims 1 to 9 for a torsion test of a composite material bar system member, characterized in that: The following steps are involved: S1. Opening a first pin hole (11) on the side wall of the rod component (1) to be tested near both ends; S2. The end plate (2) with the limiting sleeve (3) is respectively sleeved on both ends of the rod component (1), and the second pin hole (31) of the limiting sleeve (3) is aligned with the first pin hole (11); S3, inserting four pins (4) with rubber bushings (41) into the first pin hole (11) through the second pin hole (31) and reaching the end of the first pin hole (11); S4. Connect the torsion test model consisting of the anchor clamping device and the rod system component (1) to the compression-torsion test equipment through the end plate (2), and then perform the test loading.